On the Joint Symbol and Channel Estimation for Three-Hop MIMO Relaying Links - Ximenes, Leandro R. (International Journal of Advanced Engineering Research and Science, 2019)
There is a consensus that cooperative communication is a key technology for the upcoming generations of mobile communications. Whether under the Coordinated Multipoint (CoMP), Device-to-Device (D2D) communication or Internet of Things (IoT) scopes, there is little doubt that a more decentralized network, where several communicating agents smartly cooperate to improve data rate and reliability, is fundamental to cope with the always scarce resources of energy and bandwidth. When relaying stations are deployed to increase signal coverage and to provide cooperative diversity, the concatenation of two or more point-to-point MIMO channels impose a restriction on conventional algorithms for channel estimation. Although single-relay, two-hop Amplify-and-Forward (AF) systems have been reasonably investigated, there are enough evidences that more transmission hops will be a common scenario in the next years. This work proposes a semi-blind receiver for the task of joint symbol and channel estimation in a three-hop AF MIMO system. Resorting to a Nested PARAFAC tensor model, new estimating equations were derived, along studies on the uniqueness and identifiability conditions concerning the aforementioned receiver. Simulations corroborate the validity of the receiver as an effective option.